Documentary Film Festivals. Vol.1 Methods, History, Politics. Vol. 2 Changes, Challenges, Professional Perspectives. - Seguí, Isabel (Imagofagia, 2022)
Sobre Aida Vallejo y Ezra Winton. Documentary Film Festivals. Vol.1 Methods, History, Politics. Cham, Suiza: Palgrave Macmillan, 2020, 296 pp, ISBN: 978-3-030-17319-7 y Vol. 2 Changes, Challenges, Professional Perspectives. Cham, Suiza: Palgrave Macmillan, 2020. 235 pp, ISBN: 978-3-030-17323-4.